2013
DOI: 10.1074/jbc.m113.462341
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 3-mediated Necrosis via TRIF, RIP3, and MLKL

Abstract: Background: RIP3-dependent programmed necrosis is an alternative to apoptosis. Results: When caspase-8 is compromised, TRIF-dependent TLRs directly activate RIP3 kinase through RHIM-dependent interactions. Conclusion: TRIF mediates direct RHIM-dependent signaling, triggering necrosis via RIP3 and MLKL. Significance: Programmed necrosis eliminates cells following stimulation of either MyD88 or TRIF signaling pathways that converge on RIP3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
835
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 806 publications
(868 citation statements)
references
References 60 publications
26
835
4
3
Order By: Relevance
“…102,103 However, under circumstances of FADD depletion or its phosphorylation on serine residue 191 (during cell cycle arrest) or when caspases are inactivated (as occurs in virus-infected cells), IFNs can feed back on virally infected cells to activate the RNA-responsive protein kinase PKR, which then interacts with RIP1 and triggers RIP1/RIP3-mediated necroptosis. 107 When caspases are inhibited, TLR3 and TLR4 can also directly induce necroptosis by virtue of the RHIM motif of TRIF engaging RIP3 and MLKL to trigger downstream necrosis 108,109 (Figure 3). Interestingly, whereas RIP1 is required to mediate TNF-induced RIP3-dependent This leads to ubiquitination of TRAF6, TAK1/IKK-mediated activation of NFkB and induction of pro-inflammatory genes such as IL-1b and TNF.…”
Section: Rip Kinases and Tlrsmentioning
confidence: 99%
See 1 more Smart Citation
“…102,103 However, under circumstances of FADD depletion or its phosphorylation on serine residue 191 (during cell cycle arrest) or when caspases are inactivated (as occurs in virus-infected cells), IFNs can feed back on virally infected cells to activate the RNA-responsive protein kinase PKR, which then interacts with RIP1 and triggers RIP1/RIP3-mediated necroptosis. 107 When caspases are inhibited, TLR3 and TLR4 can also directly induce necroptosis by virtue of the RHIM motif of TRIF engaging RIP3 and MLKL to trigger downstream necrosis 108,109 (Figure 3). Interestingly, whereas RIP1 is required to mediate TNF-induced RIP3-dependent This leads to ubiquitination of TRAF6, TAK1/IKK-mediated activation of NFkB and induction of pro-inflammatory genes such as IL-1b and TNF.…”
Section: Rip Kinases and Tlrsmentioning
confidence: 99%
“…79 TLRs that do not employ TRIF can also induce necroptosis in an indirect manner by inducing TNF to trigger necrosis via TNFR-1 as described above. 109 In addition, some of these pathways have been associated with cell apoptosis. Overexpression of TRIF results in interaction with RIP1 and RIP3 and induction of apoptosis, 110 and in the context of TLR3 signalling in lung cancer cells, the TLR3 ligand dsRNA can induce apoptosis by recruiting caspase 8 to TLR3 in a RIP1-dependent manner.…”
Section: Rip Kinases and Tlrsmentioning
confidence: 99%
“…Mixed-lineage kinase domain-like (MLKL) is downstream of RIP3, 35,36 and phosphorylation of MLKL is required for necroptosis. [37][38][39][40][41][42] Apoptosis inducing complex (complex II) and necrosome are both supramolecular complexes. [43][44][45] A recent study showed that RIP1 and RIP3 form amyloidal fibrils through their RIP homotypic interaction motif 46 (RHIM)-mediated polymerization, and suggested that amyloidal structure is essential for necroptosis signaling.…”
mentioning
confidence: 99%
“…We also analysed primary MDFs and keratinocytes, isolated from mutant and knockout mouse strains that were deficient for cell death ligands and receptors. Fasl gld/gld Tnf -− / − and Ifnar − / − MDFs, and 29,38 We therefore generated MDFs lacking DAI, TRIF and PKR, which are known to be upregulated by interferons 39 and implicated in cell death. 29 Figure S3D).…”
Section: Resultsmentioning
confidence: 99%